Parents Education Patterns for Children In Nowadays Technology Era: A Descriptive-Analytic Study on PGSD Students of FKIP Unram - I Nyoman Karma; Ida Ermiana; Siti Istiningsih (Indonesian Publication Center, 2020)
This study aimed to find out the tendency of parents’ education patterns for children, children-expected parental education patterns in nowadays technology era, and depictions of the appropriateness between the propensity of parents’ education patterns with children expectations on parents’ education patterns. This is a survey study which emphasized on the descriptive-analytic method along with empirical approach. Stratified proportional Random Sampling was used in terms of informant determination technique. Data collection methods used: 1) interviews; 2) questionnaires; 3) library study; and 4) documentation. The result showed that: 1) authoritative education pattern was more likely to be applied by parents to their children with the highest percentage of 70.02%, the second was authoritarian 20.00%, and the third tendency was permissive by percentage of 9.98%; 2) the propensity of children-expected parental education patterns was authoritative (69.62%), permissive (17.54%), and thirdly authoritarian (12.84%); 3) there is a compatibility between parents applied educational patterns for their children and children-expected parents’ educational patterns, that is, they are both the most prominent authoritative.